2004
DOI: 10.2527/2004.8272123x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of field pea level on intake, digestion, microbial efficiency, ruminal fermentation, and in situ disappearance in beef steers fed growing diets

Abstract: Effects of increasing level of field pea (variety: Profi) on intake, digestion, microbial efficiency, and ruminal fermentation were evaluated in beef steers fed growing diets. Four ruminally and duodenally cannulated crossbred beef steers (367+/-48 kg initial BW) were used in a 4 x 4 Latin square. The control diet consisted of 50% corn, 23% corn silage, 23% alfalfa hay, and 4% supplement (DM basis). Treatments were field pea replacing corn at 0, 33, 67, or 100%. Diets were formulated to contain a minimum of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…Because of the greater DMI of the control group, a greater ruminal VFA concentration was expected in this group; however, DMI did not affect the total VFA concentration. Similar results were found in the study of Reed et al (2004), in which ruminal VFA concentration was not affected by the substitution of corn grain with field peas. Soto-Navarro et al (2004) did not report differences on fermentative parameters when field pea levels increased.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Because of the greater DMI of the control group, a greater ruminal VFA concentration was expected in this group; however, DMI did not affect the total VFA concentration. Similar results were found in the study of Reed et al (2004), in which ruminal VFA concentration was not affected by the substitution of corn grain with field peas. Soto-Navarro et al (2004) did not report differences on fermentative parameters when field pea levels increased.…”
Section: Resultssupporting
confidence: 89%
“…In another study, in which different legume grains were included in diets of feedlot beef cattle, it was reported that the presence of these ingredients decreased ruminal VFA concentration (Gilbery et al, 2007). Reed et al (2004), however, reported that inclusion of field peas linearly decrease acetate molar proportion and do not have an effect on propionate and butyrate molar proportions. Contrary to the results presented in the present study, Gilbery et al (2007) found that inclusion of legume grains decrease acetate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…No differences in feed intake were observed between individual experimental groups or between experimental groups and control group. VALENTINE and BARTSCH (1987) and MESSMAN et al (1992) reported a positive effect of peas on the overall intake of dry mass in dairy cows; similar results were found by REED et al (2004) in bulls. LOSAND et al (2003) recommend feeding no more than 4,0 kg of peas per day and one dairy cow.…”
Section: Methodssupporting
confidence: 70%
“…The present results may be explained by the high digestibility of OM of oat hay with TFB concentrate rumen conditions and was probably due not only to faba bean seeds but also to the high level of inclusion of triticale (71 % DM) in the concentrate (Klassen and Hill, 1971). Reed et al (2004) observed that the replacement of corn with field pea in concentrate did not affect starch digestibility. The estimated gas production from the immediately soluble fraction (a) was similar to that reported by Ahmed and El-Hag (2004), who found a similar negative value with 14 Sudanese plant species incubated in the rumen of ewes and attribute it to the lag phase during which microorganisms attach and colonize food particles before their degradation.…”
Section: In Vitro Gas Productionmentioning
confidence: 93%